CTAB-assisted synthesis of dissilient hollow spherical MoS2 for efficient hydrogen evolution. (5th December 2018) - Jiang, Youxiang; Wang, Jie; Zhang, Dongen; Luo, Yuhui; Yang, Tang; Gong, Junyan; Zhang, Fan; Zhang, Xiaobo; Tong, Zhiwei
Abstract: Dissilient hollow spherical MoS2 was prepared by one-step hydrothermal method using cetyltrimethyl ammonium bromide (CTAB) as a surfactant. The structure and morphology of the prepared materials were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The addition of CTAB plays an important role in controlling the morphology of MoS2 . As the amount of CTAB was increased, the morphology of MoS2 changed from flake to hollow sphere and finally broked up. Compared with MoS2 without CTAB and closed hollow spherical MoS2, the dissilient hollow spherical MoS2 showed better electrochemical performance in the hydrogen evolution reaction (HER) and good stability after 1000 cycles. We attribute this improvement to large specific surface area and many catalytic active sites of the dissilient hollow spheres. In general, the optimized catalyst exhibited an onset overpotential of 159 mV, a low Tafel slope of 65 mV dec −1, and relatively good stability.